2022
DOI: 10.1371/journal.pone.0261544
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation chimeras provide evidence of in vivo intercellular correction in ovine CLN6 neuronal ceroid lipofuscinosis (Batten disease)

Abstract: The neuronal ceroid lipofuscinoses (NCLs; Batten disease) are fatal, mainly childhood, inherited neurodegenerative lysosomal storage diseases. Sheep affected with a CLN6 form display progressive regionally defined glial activation and subsequent neurodegeneration, indicating that neuroinflammation may be causative of pathogenesis. In this study, aggregation chimeras were generated from homozygous unaffected normal and CLN6 affected sheep embryos, resulting in seven chimeric animals with varied proportions of n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Mondo et al (2018) have studied the neuronal uptake and distribution of three adeno-associated virus (AAV) therapies, while Pfister et al (2018) showed that AAV9 can safely silence human mutant HD protein [58,59] . Texel-cross [69] Gene editing Enzyme Replacement Therapy [70] N/A It produces common phenotypical human disease characteristics CLN5 [71] New Zealand Borderdale Natural Gene Therapies [72,73] 11-12 months [74] In a comparative EEG study, CLN5 homozygous sheep present sleep abnormalities comparable to the brain activity of epileptic children [75] They manifest similarity to the molecular pathways of synapse pathophysiology with less developed animals (mouse and Drosophila models), allowing for target therapeutics on a larger animal [60] CLN6 [71,76] 1…”
Section: Neuronal Ceroid Lipofuscinosis (Batten Disease)mentioning
confidence: 99%
“…Mondo et al (2018) have studied the neuronal uptake and distribution of three adeno-associated virus (AAV) therapies, while Pfister et al (2018) showed that AAV9 can safely silence human mutant HD protein [58,59] . Texel-cross [69] Gene editing Enzyme Replacement Therapy [70] N/A It produces common phenotypical human disease characteristics CLN5 [71] New Zealand Borderdale Natural Gene Therapies [72,73] 11-12 months [74] In a comparative EEG study, CLN5 homozygous sheep present sleep abnormalities comparable to the brain activity of epileptic children [75] They manifest similarity to the molecular pathways of synapse pathophysiology with less developed animals (mouse and Drosophila models), allowing for target therapeutics on a larger animal [60] CLN6 [71,76] 1…”
Section: Neuronal Ceroid Lipofuscinosis (Batten Disease)mentioning
confidence: 99%